ANALISIS EFISIENSI TEORETIS KONDISI FABRIC FILTER DI UNIT COAL MILL PADA PT SG DI TUBAN JAWA TIMUR - Huboyo, Haryono Setiyo (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2007)
Cement  Industrial  activities  produces  various  pollutants  mainly  dust  pollutant  and  gases pollutants. These  pollutants  come  up  from  material  handling,  production  process  (treatment, combustion  and finish  mill)  and  packing  process.  PT  SG  has  done  any  steps  to  controll  its pollutant  i.e  ambient and  emission  pollutant  measurements  and  conducting  abatement.  Bag filters in coal mill unit shows an excellent performance since its real dust output concentration only 22.9 and 13.4 mg/m3 far below emission standard 80 mg/m3. Theoretical efficiency of this device  was  assessed  using  design  criteria, limited  assumption  and  secondary  relevant literature.  Based  on  secondary  data  the  efficiency  was 99.9%  (higher  than  EPA  standard 99.5%). Its values are somewhat different using real output concentration showing 99.29% and 99.58%.  These  differences  were  subjected  to  limited  design specification  data  and  fluid properties exist.